The return of ancestral gods : modern Ukrainian Paganism as an alternative vision for a nation - Lesiv, Mariya, 1978- (McGill-Queen's studies in the history of religion., 2013)
How socio-political turmoil has inspired a new religious movement based on the imagined past.